Computational analysis of heat transfer in fluids and solids II : special topic volume with invited peer reviewed papers only - Makinde, Oluwole Daniel (Diffusion and defect data. Defect and diffusion forum, 2020)
Special topic volume with invited peer-reviewed papers only.